Noninvasive Brain Stimulation for Improving Cognitive Deficits and Clinical Symptoms in Attention-Deficit/Hyperactivity Disorder: A Systematic Review and Meta-Analysis - Yao Yin; Xueke Wang; Tingyong Feng (Brain Sciences)
Objective: Noninvasive brain stimulation (NIBS) is a promising complementary treatment for attention-deficit/hyperactivity disorder (ADHD). However, its efficacy varies due to diverse participant profiles and methodologies. This meta-analysis, registered with PROSPERO (CRD42023457269), seeks to assess NIBS efficacy in improving cognitive deficits and clinical symptoms in individuals with ADHD. Methods: We systematically searched five databases (October 2024) for randomized controlled trials focusing on cognitive functions and clinical symptoms in individuals meeting the DSM/ICD criteria for ADHD. A meta-analytical synthesis was conducted using RevMan 5.4.1. Results: Meta-analyses found significant improvement in inhibitory control, working memory, and inattention in active transcranial direct current stimulation (tDCS) groups compared with sham groups. Conversely, repetitive transcranial magnetic stimulation (rTMS) did not demonstrate significant therapeutic benefits for ADHD symptoms. Additionally, four transcranial random noise stimulation (tRNS) and three transcranial alternating current stimulation (tACS) studies demonstrated promising improvements in executive functions and the alleviation of ADHD symptoms. Conclusions: The findings from this meta-analysis highlight NIBS as a promising adjunctive therapy for managing ADHD, advancing both theoretical knowledge and practical treatment options in this field.